Ultrasonography feature and Clinical Finding of Trisomy 13 (Patau Syndrome): A Case Report - Melissa Edelweishia; I Wayan Artana Putra (Indonesian Journal of Obstetrics & Gynecology Science)
Background: Trisomy 13 is a trisomy disorder of chromosome 13 which causes many fetal structural defects. The prognosis is very poor and the majority is still birth. Major structural anomalies are occasionally identified in the late-first or early-second trimester. Any discovery of multiple structural anomalies in the fetus increases the chances of chromosomal anomalies. Case Report: Here we report trisomy 13 case of A 34-years-old housewife, third gravida, prenatal diagnosis during antenatal ultrasonography showed diaphragmatic hernias, cardiovascular dextroposition, ventricular septal defect, labiognatopalatoschizis and renal dextra pyeletaxis. From the chromosomal analysis, the fetal karyotype was 47 XY+13. A male infant was born with weight of 2600 grams, 46 cm, cyanosis, and severe respiratory distress with congenital abnormalities of micrognathia, diaphragmatic hernia, dextrocardia, ventricular septal defect, persistent pulmonary hypertension of newborn, undescended testis, labiognatopalatoshizis, and polydactily. Discussion: Prenatal diagnosis can be done through amniocentesis for karyotyping which is the gold standard for diagnosis trisomy 13. In addition, screening can also be done since the first trimester.Conclusion: All pregnancies in second trimester must be evaluated for structural abnormalities through ultrasonography and cytogenetic examination if necessary for early diagnosed.Key word: Congenital Abnormalities, Ultrasonography, Clinical Finding, Trisomy 13, Patau SyndromeAbstrakLatar Belakang: Trisomi 13 merupakan kelainan jumlah kromosom 13 yang menyebabkan defek struktural pada fetus. Prognosisnya sangat buruk dan kebanyakan lahir mati. Kelainan struktural mayor sering teridentifikasi pada akhir trimester pertama atau awal trimester kedua. Setiap temuan kelainan struktural pada fetus berpotensi kelainan kromosom.Laporan Kasus: Di sini akan dijelaskan kasus trisomi 13 yang didiagnosis prenatal dari wanita G3P1011, 34 tahun, terdiagnosis melalui pemeriksaan ultrasonografi. Antenatal scan dilakukan pada usia kehamilan 21 minggu dan gambaran ultrasonografi menunjukkan hernia diafragmatika, dextrokardia, ventricular septal defect, labiognatopalatoschizis dan pielektasis ginjal kanan. Kemudian dilanjutkan pemeriksaan kromosom melalui amniosintesis dan didapatkan hasil 47 XY+13.  Bayi laki-laki lahir secara sectio secarea dengan berat 2600 gram, panjang badan 46 cm, sianosis, asfiksia berat, kelainan kongenital micrognatia, hernia diafragmatika, dextrokardia, defek septum ventrikular, hipertensi pulmonal, labiognatopalatoshizis, dan polidactili. Diskusi: Diagnosis prenatal dapat dilakukan melalui pemeriksaan amniosintesis bertujuan untuk melihat karyotyping yang merupakan gold standard untuk mendiagnosis  trisomi 13. Selain itu, screening juga dapat dikerjakan sejak trimester pertama.Kesimpulan: Semua kehamilan pada trimester kedua harus dievaluasi kelainan struktural melalui ultrasonografi dan bila perlu pemeriksaan sitogenetik sehingga dapat mendiagnosis lebih awal.Kata kunci: Kelainan Kongenital, Ultrasonografi, Klinis, Trisomi 13, Patau Sindrom.